2015
DOI: 10.1016/j.jobcr.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of healing after gingivectomy with electrocautery and laser

Abstract: Both techniques with proper adhesion to safeguards, can be used to remove gingival overgrowth with equal efficiency and wound healing capacity. There is no advantage of diode laser over electrocautery in performing gingivectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 8 publications
4
19
1
5
Order By: Relevance
“…In laser side five patients showed no instrument sticking and the other five required gentle grasping for removal of tissues from the instrument, while all patients in electrocautery sides showed tissue sticking to the instrument tips which required gentle grasping for removal. This is in contrast to the results of Kumar et al 2015 23 , who found more tissue sticking on laser side than electrocautery side with easier cutting procedure. However this occurs with cases having thick and deep overgrown tissues, while in less thick tissue cases laser was much easier to use with less sticking on its tip.…”
Section: Disscusioncontrasting
confidence: 96%
See 2 more Smart Citations
“…In laser side five patients showed no instrument sticking and the other five required gentle grasping for removal of tissues from the instrument, while all patients in electrocautery sides showed tissue sticking to the instrument tips which required gentle grasping for removal. This is in contrast to the results of Kumar et al 2015 23 , who found more tissue sticking on laser side than electrocautery side with easier cutting procedure. However this occurs with cases having thick and deep overgrown tissues, while in less thick tissue cases laser was much easier to use with less sticking on its tip.…”
Section: Disscusioncontrasting
confidence: 96%
“…However, healing scores throughout the follow up period was in favor of laser therapy sides. These results agree with the results reported by Kuram et al 2015 23 who found no significant differences between laser and electrocautery gingivectomy groups regarding wound healing at 24 h, 72 h, 1, 2, 4 weeks postoperatively. However, fibrinous slough and charring exist in both groups with more charring present at the laser sides.…”
Section: Disscusionsupporting
confidence: 93%
See 1 more Smart Citation
“…Plak boyama ajanı dişeti yaralarının yüzeyini değerlendirmek için kullanıldı. Plak boyama ajanının yanısıra, iyileşme indeksi, biyokimyasal parametreler, fotoğrafların morfometri k ve/veya bilgisayar destekli değerlendirilmesi, büyütmeyle değerlendirme ve histolojik tetkik de iyileşmenin değerlendirilmesi için kullanılabilir 9,17,[32][33][34][35][36][37] . Bu çalışmada yara fotoğrafları plak boyama ajanı uygulandıktan sonra yaraların fotoğrafları alındı ve değerlendirme için bir dijital görüntü programı kullanıldı.…”
Section: Discussionunclassified
“…Ağrı ölçümü için çeşitli metodlar bulunmaktadır. Bunlardan en sık tercihe dileni VAS'tır 17,26,34,[37][38][39] . Bu çalışmada postoperatif ağrı VAS ile değerlendirildi.…”
Section: Discussionunclassified